Assia Djebar et la réécriture de l’histoire au féminin - Nancy Ali (Multilinguales)
Assia Djebar and the Rewriting of the History in the FeminineIn L’Amour, la fantasia, Assia Djebar lends a hand to the voiceless, the illiterate women of the Algerian war, transmitting their oral testimonies in her French text. We argue that Djebar negotiates a specific place between an anonymous autobiography and a collective one for the female autobiography written in a society that frowns upon the first-person pronoun of a woman. We address the author’s role as a storyteller: revisiting the French archives of the conquest of Algeria, Djebar gives a voice to the stories of the otherwise silenced women. We explore how writing for Djebar is a means of coming to life, not just for herself, but also for the women of Algeria whose stories she inscribes in the narrative of History. So doing, she rewrites History into a feminized palimpsest.